Synthesis of molecularly imprinted polymer for the removal of cyanazine from aqueous samples - Rachel Marcella, Roland; Showkat Ahmad, Bhawani; Mohamad Nasir, Mohamad Ibrahim (BioMed Central Ltd., 2023)
Background Cyanazine (CYZ) is one of the triazine herbicides to prevent broadleaf grass and weeds in crops. Despite its afordability and productivity in increasing crop yield, the extensive usage of CYZ contributes to environmental pollution and poses risks to living organisms. Most research has focused on detecting CYZ in the environment and its toxicity to humans and the ecosystem. For these reasons, molecular imprinting technology (MIT) can be applied to produce an efective adsorbent material of high binding afnity and selectivity towards its target compound which is known as molecularly imprinted polymers (MIPs). In this study, MIP was prepared by precipitation polymerization using CYZ as a template molecule, methacrylic acid (MAA), acrylamide (AAm) and 4-vinylpyridine (4VP) as functional monomers, and ethylene glycol dimethacrylate (EGDMA) as cross-linker in the ratio of 1:6:12, respectively. The effects of contact time, initial concentration, pH, and polymer dosages on the adsorption efciencies of MIPs were also investigated in this study. Results MIPs of CYZ were successfully synthesized by precipitation polymerization method with a non-covalent approach using diferent functional monomers such as methacrylic acid (MAA), acrylamide (AAm) and 4-vinylpyridine (4VP). For the comparison study, the non-imprinted polymer (NIP) was synthesized without the addition of CYZ, the template molecule. The FTIR analysis indicated the interactions among CYZ and functional monomers (MAA, AAm or 4VP) in the presence of EGDMA as a cross-linker. The FESEM analysis showed that only MIP (AAm) and NIP (AAm) had regular and spherical polymer particles while MIP (MAA), NIP (MAA), MIP (4VP) and NIP (4VP) were agglomerated and irregular in shape. The EDX analysis showed that the MIPs were mainly composed of carbon and oxygen. Meanwhile, the BET analysis of MIP (AAm) had higher surface area, total pore volume and average pore radius than that NIP (AAm). Based on the batch binding study, MIP (AAm) (83.30%) had the highest binding efciency than the MIP (MAA) (76.96%) and MIP (2VP) (76.90%) at a contact time of 240 min. The optimum conditions for the highest binding efciency of MIP (AAm) were obtained at an initial concentration of 6 ppm, pH 7 and polymer dosage of 0.1 g polymer beads. The adsorption efciency of MIP (AAm) with CYZ at the optimum parameters resulted in 86.39%. The selectivity test showed that MIP (AAm) was more selective towards CYZ than AME, the competitive compound with relative selectivity coefcient of 2.36. The kinetic isotherm of MIP (AAm) was best explained according to the pseudo-secondorder kinetic model while the adsorption isotherm of MIP (AAm) was based on the Langmuir adsorption isotherm model. The MIP (AAm) was tested in the distilled water (DIW), tap water and river water spiked with CYZ and a substantial amount of CYZ was removed with a recovery of 86.67%, 84.75% and 84.69%, respectively. Conclusion The MIPs of CYZ were successfully synthesized by the precipitation polymerization method using different functional monomers. Among those MIPs, MIP (AAm) showed the highest rebinding efciency and therefore this MIP was selected for further studies. The best combination of CYZ, AAm was the main factor that contributed to the morphological and chemical properties, as well as the efciency and selective binding performance of MIP (AAm). Since MIP (AAm) showed a substantial removal efciency of CYZ in the environment specifcally water sources, it has the capability to act as an adsorbent material for various purposes such as solid-phase extraction techniques and a stationary phase in various chromatographic techniques.